Development of Snakes and Ladders Media for Vocabulary Learning in Grade VIII Students of SMP Darussalam Kademangan - Iksanudin, Moh.; Hadi, Saptono; Hermawan, Agus; Sa’diyah, Lailiyatus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
Language plays a crucial role in developing human potential across various domains of life. However, many students still have limited vocabulary mastery, especially in understanding synonyms, antonyms, and analogies, which presents a significant learning challenge. Therefore, engaging and motivating learning media are needed to support vocabulary development. This study employed the Research and Development (R&D) method to create and validate Snakes and Ladders game media for vocabulary learning in Grade VIII students of SMP Darussalam Kademangan. Instrument validation results showed that all statement items had correlation values exceeding the r-table value of 0.497 at a 5% significance level with 16 respondents, indicating good validity. Reliability testing using Cronbach’s Alpha yielded a coefficient of 0.917, classified as “very good.” Media expert validation produced a score of 95%, signifying that the media is highly feasible for use. Student response questionnaires resulted in a score of 82%, categorized as “good,” further supporting the feasibility and acceptability of the developed product. Overall, the Snakes and Ladders game media proved effective and feasible for enhancing vocabulary learning among Grade VIII students.